G6PDH as a key immunometabolic and redox trigger in arthropods - Moraes, Bruno; Martins, Renato; Lopes, Cintia; Martins, Ronald; Arcanjo, Angélica; Nascimento, Jhenifer; Konnai, Satoru; da Silva Vaz, Itabajara; Logullo, Carlos (Frontiers in Physiology, 2023)
The enzyme glucose-6-phosphate dehydrogenase (G6PDH) plays crucial roles in glucose homeostasis and the pentose phosphate pathway (PPP), being also involved in redox metabolism. The PPP is an important metabolic pathway that produces ribose and nicotinamide adenine dinucleotide phosphate (NADPH), which are essential for several physiologic and biochemical processes, such as the synthesis of fatty acids and nucleic acids. As a rate-limiting step in PPP, G6PDH is a highly conserved enzyme and its deficiency can lead to severe consequences for the organism, in particular for cell growth. Insufficient G6PDH activity can lead to cell growth arrest, impaired embryonic development, as well as a reduction in insulin sensitivity, inflammation, diabetes, and hypertension. While research on G6PDH and PPP has historically focused on mammalian models, particularly human disorders, recent studies have shed light on the regulation of this enzyme in arthropods, where new functions were discovered. This review will discuss the role of arthropod G6PDH in regulating redox homeostasis and immunometabolism and explore potential avenues for further research on this enzyme in various metabolic adaptations.